RUSSIAN MEDICAL UNIVERSITIES IN INTERNATIONAL RANKINGS: COMPARISON OF SCIENTOMETRIC CRITERIA - M. B. Khrustalev; N. Yu. Turbina; A. A. Maksimova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Currently, globalization and market economy have led to the necessary improving competitiveness of the universities. The parameters of academic efficiency along with reputation indicators become the main criteria for inclusion in international and domestic rankings and thus affect the financial well-being of the university.The objective of this study is to compare the indicators of scientific activity of the largest Russian medical universities and the foreign non-English speaking university that conducts training in medicine, according to data obtained from scientometric databases and to determine the prospects for including Russian medical universities into the leading international rankings.Material and methods. The publication activity of 9 largest Russian medical universities for 5 years was analyzed: the number of articles and the number of citations. For comparison, we used data from a similar number of employees of a foreign university that trains students in medicine, included in international rankings. The sources were the Scopus database, as well as international rankings: Times Higher Education, Academic Ranking of World Universities and QS World University Rankings.Results. Only two Russian medical universities are mentioned in the bottom lines (1000+) in the THE ranking and none of them fall into the QS WUR ranking. However, while maintaining the current trends of increasing the number of publications in Scopus, in the next 2–3 years there are prospects for inclusion in the THE ranking of «Pavlov First Saint Petersburg State Medical University» and «A. I. Yevdokimov Moscow State University of Medicine and Dentistry». Conclusion. Based on the analysis of publication activity of the largest medical universities in Russia, it can be noted that it is necessary to develop international scientific cooperation and develop strategies for improving self citation in universities, and also need to work more actively with graduates and their employers.